Preoperative Risk and the Association between Hypotension and Postoperative Acute Kidney Injury. (March 2020) - Mathis, Michael R.; Naik, Bhiken I.; Freundlich, Robert E.; Shanks, Amy M.; Heung, Michael; Kim, Minjae; Burns, Michael L.; Colquhoun, Douglas A.; Rangrass, Govind; Janda, Allison; Engoren, Milo C.; Saager, Leif; et al.
Abstract : Background: Despite the significant healthcare impact of acute kidney injury, little is known regarding prevention. Single-center data have implicated hypotension in developing postoperative acute kidney injury. The generalizability of this finding and the interaction between hypotension and baseline patient disease burden remain unknown. The authors sought to determine whether the association between intraoperative hypotension and acute kidney injury varies by preoperative risk. Methods: Major noncardiac surgical procedures performed on adult patients across eight hospitals between 2008 and 2015 were reviewed. Derivation and validation cohorts were used, and cases were stratified into preoperative risk quartiles based upon comorbidities and surgical procedure. After preoperative risk stratification, associations between intraoperative hypotension and acute kidney injury were analyzed. Hypotension was defined as the lowest mean arterial pressure range achieved for more than 10 min; ranges were defined as absolute (mmHg) or relative (percentage of decrease from baseline). Results: Among 138, 021 cases reviewed, 12, 431 (9.0%) developed postoperative acute kidney injury. Major risk factors included anemia, estimated glomerular filtration rate, surgery type, American Society of Anesthesiologists Physical Status, and expected anesthesia duration. Using such factors and others for risk stratification, patients with low baseline risk demonstrated no associations between intraoperative hypotension and acute kidney injury. Patients with medium risk demonstrated associations between severe-range intraoperative hypotension (mean arterial pressure less than 50 mmHg) and acute kidney injury (adjusted odds ratio, 2.62; 95% CI, 1.65 to 4.16 in validation cohort). In patients with the highest risk, mild hypotension ranges (mean arterial pressure 55 to 59 mmHg) were associated with acute kidney injury (adjusted odds ratio, 1.34; 95% CI, 1.16 to 1.56). Compared with absolute hypotension, relative hypotension demonstrated weak associations with acute kidney injury not replicable in the validation cohort. Conclusions: Adult patients undergoing noncardiac surgery demonstrate varying associations with distinct levels of hypotension when stratified by preoperative risk factors. Specific levels of absolute hypotension, but not relative hypotension, are an important independent risk factor for acute kidney injury. Abstract : In a large cohort of noncardiac surgical patients, the incidence of acute kidney injury was 9%. Major factors identifying patients at risk for acute kidney injury included anemia, estimated glomerular filtration rate, elevated risk surgery, American Society of Anesthesiologists Physical Status, and expected anesthesia duration. The relationship between hypotension and acute kidney injury varied by underlying patient and procedural risk. Patients with low risk demonstrated no associated increased risk of acute kidney injury across all blood pressure ranges, whereas patients with the highest baseline risk demonstrated an association between even mild absolute intraoperative hypotension ranges and acute kidney injury.Supplemental Digital Content is available in the text.